Mixed Phenotype Acute Leukemia Presenting as Leukemia Cutis - Geetha Narayanan; M. T. Sugeeth; Lali V. Soman (Case Reports in Medicine)
Leukemia cutis (LC) is defined as infiltration of the skin by leukemic cells resulting in clinically recognizable cutaneous lesions. It is common in congenital leukemia and acute myeloid leukemia. However, LC has rarely been reported with mixed phenotypic acute leukemia (MPAL). We report the case of a lady who presented with erythematous papular and nodular lesions all over the body. Skin biopsy showed leukemic infiltration and bone marrow aspiration showed MPAL of the T/myeloid with monocytic differentiation lineage. This is the first report of an adult patient with MPAL of the T/myeloid with monocytic differentiation type presenting with leukemia cutis. She was started on chemotherapy with Hyper-CVAD. There is complete resolution of the skin lesions and she has achieved bone marrow remission after the first cycle of chemotherapy.